Development of HOTS-based biology learning documents using ADDIE Model - Enies Nabila Fithri Tiara Sari; M. Amin; Atok Miftachul Hudha; Diani Fatmawati; Ahmad Fauzi (Research and Development in Education (RaDEn), 2021)
Empowerment of Higher-Order Thinking Skills (HOTS) is often not optimal due to the lack of availability of HOTS-based learning documents. The purpose of this development research was to produce HOTS-based biology learning tools on motion system material for class XI high school. This development research uses the ADDIE model which has five stages: analyze, design, develop, implement and evaluate. The product development was validated by learning experts and material experts and then tested on students. The validation sheet was used as a data collection instrument. The validation results from learning experts stated that the learning syllabus was very feasible (84.3%), lesson plans were very feasible (80.2%), student worksheets were feasible (72.2%), and test questions were very feasible (83%). Meanwhile, the validation results from material experts stated that all learning documents were feasible (the percentage of eligibility for syllabus, lesson plans, student worksheets, and test questions were 77%, 70%, 80%, and 80%, respectively). After being tested on students, student responses and the results of their evaluation scores indicate that the learning documents that have been developed are suitable for use. In addition, the HOTS learning tools developed are practical and effective in the learning process, so as to create a student-centered learning process and be able to improve students' HOTS.